Evaluating an enhanced three-dimensional electrode system for the remediation of Cr(Ⅵ)-contaminated clay: Detoxification efficiency and soil resilience - Zihong Bian; Honghui Wu; Xinyi Lan; Yanran Wang; Tianxiang Tong; Xiaohua Fu; Yijie Zhu; Meiying Jia; Xiong Yang; Haiyin Xu; Yuanling Luo; Zhengyong Xu; et al. (Journal of Environmental Chemical Engineering, 2026)

Insight into peroxymonosulfate activation by biochar-derived dissolved organic matter toward in-situ sustainable groundwater remediation: The role of active functional groups and efficient electron shuttles - Xinling Ye; Chenxi Wang; Qin Shi; Chuanqi Zhao; Honghui Pan; Yan Liu; Xixiang Liu (Journal of Cleaner Production, 2026)

Inulin alleviates metabolic dysfunction-associated steatotic liver disease-induced bone loss potentially by activating the Nrf2/GPX4 signaling pathway - Shaobo Gu; Junzhuo Wang; Kangpeng Zhong; Xuejie Yao; Jinfeng Wen; Dahua Chen; Deyi Yan; Zongkai Zhang; Honghui Chen; Xiaoyun Ding; Siyi Yu; Yi Chen; et al. (Molecular and Cellular Biochemistry, 2026)

Supported Co-Zr-B catalysts for hydrogen generation from the hydrolysis of NaBH4 solution - Wenjing Liu; Yuzhu Zhao; Honghui Chen; Yuntong Wang; Yutong Han; Xinpeng Yang; Yan Wang; Ke Zhang; Zhongqiu Cao; Yan Gao; Shiwei Wu; Shuchong Bai (Fuel, 2026)

Low-velocity impact response of bio-inspired multi-sinusoidal corrugated sandwich structure - Jing Sun; Honghui Li; Haikun Peng; Chao Ding; Lewei Yan; Xinmei Xiang (Engineering Structures, 2026)

Microencapsulation mechanism of menthol and menthone by hydroxypropyl-β-cyclodextrin for enhanced stability and prolonged retention - Honghui Guo; Haohong Yao; Quanxing Zheng; Quanling Xie; Hongliang Lu; Xiaohua Deng; Yan Lin; Ming’en Zhang; Pengfei Ma; Zhuan Hong; Xiaoqing Huang (Food and Bioproducts Processing, 2026)

Permian-Triassic adakitic rocks in the Changchun-Yanji Suture, NE China: Constraints on the eastern extension of the Solonker Suture and Paleo-Asian Ocean closure - Honghui Wang; Xinghua Ma; Jinyu Yan; Simon A. Wilde (Lithos, 2025)

Photocatalytic degradation of diclofenac using aluminium oxide modified photocatalyst derived from iron-rich sludge - Chenxu Wang; Shihao Ni; Yan Liu; Honghui Pan; Qin Shi; Chuanqi Zhao; Xixiang Liu (Journal of Environmental Chemical Engineering, 2025)

An intelligent polybutylene terephthalate adipate (PBAT)-based packaging film incorporating functionalized chitin microcapsules as a freshness indicator for shrimp monitoring - Honghui Guo; Jie Zhang; Jian Gao; Ziyu Liang; Wei Li; Hong Yan; Ruijie Guo; Huifang Wang (Food Bioscience, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Decoupling of tungsten and tin mineralization governed by magmatic fluorine - Xinghua Ma; Jinyu Yan; Honghui Wang; Reimar Seltmann (Science China Earth Sciences, 2025)

Insight into in-situ Fenton-like catalysis by iron-rich sludge-derived iron-carbon composites: Molecular oxygen activation driven by electron transfer in Fe-C structure - Zhuowen Li; Liying Liang; Wen Tan; Yan Liu; Honghui Pan; Qin Shi; Chuanqi Zhao; Shiyong Huang; Xixiang Liu (Journal of Environmental Chemical Engineering, 2025)

Extreme Drought Decreases the Stability of Above‐ but Not Below‐Ground Productivity Across Eurasian Steppes - Yingjie Yan; Chong Xu; Yann Hautier; Hongqiang Wang; Yuguang Ke; Honghui Wu; Jinsong Wang; Changjin Cheng; Xiaoan Zuo; Wentao Luo; Melinda D. Smith; Alan K. Knapp; et al. (Global Change Biology, 2025)
Ecological stability plays a crucial role in determining the sustainability of ecosystem functioning and nature's contribution to people. Although the disruptive effects of extreme drought on ecosystem structure and functions are widely recognized, their effect on the stability of above‐ and belowground productivity remains understudied. We assessed the effects of drought on ecosystem stability using a 3‐year drought experiment established in six Eurasian steppe grasslands. The treatments imposed included ambient precipitation, chronic drought (66% reduction in precipitation throughout the growing season), and intense drought (complete exclusion of precipitation for two months during the growing season). We found that drought, irrespective of how it was imposed, reduced the stability of aboveground net primary productivity (ANPP) but had little impact on belowground net primary productivity (BNPP) stability. Reduced ANPP stability under drought was primarily attributed to changes in subordinate species stability, with mean annual precipitation (MAP) and its variability, historical drought frequency, and the aridity index (AI) also influencing responses to extreme drought. In contrast, BNPP stability was not related to any community factor investigated, but it was influenced by MAP variability and AI. Our findings that above‐ and belowground productivity stability in grasslands are differentially sensitive to multi‐year extreme drought under both common (MAP and AI) as well as unique drivers (plant community changes) highlight the complexity of predicting carbon cycle dynamics as hydrological extremes become more severe.

Genome-wide association analysis reveals genetic architecture of growth and inner shell color traits in freshwater pearl mussel Hyriopsis cumingii (Lea 1852) - Zhiyan Wang; Honghui Hu; He Wang; Ling Yan; Yao Zhang; Hao Wang; Xuefeng Lv; Jiale Li; Zhiyi Bai (Aquaculture, 2025)

Insight into the sulfite activation by Fe-rich sludge-derived biochar for efficient organic contaminant degradation: The role of iron species - Xixiang Liu; Xinyi Shi; Mingjian Huang; Honghui Pan; Yan Liu; Liying Liang; Chuanqi Zhao; Shiyong Huang; Tieguang He (Journal of Water Process Engineering, 2024)

Enhanced dewaterability of waste activated sludge via peroxymonosulfate activation process initiated by magnetic biochar derived from iron-rich sludge - Xixiang Liu; Fuyu Luo; Liying Liang; Nan Li; Zheng Zhou; Yan Liu; Honghui Pan (Sustainable Chemistry and Pharmacy, 2024)

Quercetin analogs as α-glucosidase inhibitors with antidiabetic activity - Honghui Liu; Yan Wang; Jing Tong; Jing Li; Hong Ding (Food Bioscience, 2024)

Self-endowed magnetic photocatalysts derived from iron-rich sludge and its recycling in photocatalytic process for tetracycline degradation - Xixiang Liu; Hengyi Wang; Chenxu Wang; Liyang Zhao; Honghui Pan; Yan Liu; Liying Liang; Chuanqi Zhao; Shiyong Huang (Bioresource Technology, 2024)

Effect of Aspergillus flavus contamination on the fungal community succession, mycotoxin production and storage quality of maize kernels at various temperatures - Honghui Shi; Jiaxin Li; Yan Zhao; Jiangdi Mao; Haifeng Wang; Junli Zhu (Food Research International, 2023)

Modeling density-driven flow in porous media by physics-informed neural networks for CO2 sequestration - Honghui Du; Ze Zhao; Haojia Cheng; Jinhui Yan; QiZhi He (Computers and Geotechnics, 2023)

Vocalization Behavior of Chinese Bahaba (Bahaba taipingensis) during the Reproduction Season - Hongquan Li; Zhongchang Song; Jiangang Hui; Yingnan Su; Weijie Fu; Shufei Zhang; Lin Yan; Kuoqiu Yan; Honghui Huang; Yu Zhang (Journal of Marine Science and Engineering, 2023)
Chinese bahaba (Bahaba taipingensis) is a critically endangered fish species, which can produce sounds like other Sciaenidae species. In this study, sounds produced by sexually mature Chinese bahaba were recorded during the reproduction season for the first time. Two distinct types of sounds were observed during the reproduction season, termed as single drum and fast drum trains calls. Single drum callings occurred as a series of trains with rapid pulses, while fast drum trains callings were mainly made of a single signal. The single drum and fast drum trains had a peak frequency of 77.8 ± 16.2 Hz and 79.1 ± 8.7 Hz, respectively. Statistical analysis suggested significant differences in −3 dB bandwidth, signal duration, and root-mean-square sound pressure levels, except for peak frequency (p

Erratum to: Estimate of Hydrofluorocarbon Emissions for 2012–16 in the Yangtze River Delta, China - Jingjiao Pu; Honghui Xu; Bo Yao; Yan Yu; Yujun Jiang; Qianli Ma; Liqu Chen (Advances in Atmospheric Sciences, 2020)

Estimate of Hydrofluorocarbon Emissions for 2012–16 in the Yangtze River Delta, China - Jingjiao Pu; Honghui Xu; Bo Yao; Yan Yu; Yujun Jiang; Qianli Ma; Liqu Chen (Advances in Atmospheric Sciences, 2020)

NAP is involved in GA-mediated chlorophyll degradation and leaf senescence by interacting with DELLAs in Arabidopsis - Wei Lei; Yan Li; Xiuhong Yao; Kang Qiao; Lin Wei; Baohui Liu; Dawei Zhang; Honghui Lin (Plant Cell Reports, 2020)

What We Can Learn from Current Inflammatory Bowel Disease (IBD) Biological Therapy—Dose Regimen and Others - Yan Xu; Aditi Sharma; Yang Chen; Honghui Zhou (Current Pharmacology Reports, 2019)

Joint longitudinal model development: application to exposure–response modeling of ACR and DAS scores in rheumatoid arthritis patients treated with sirukumab - Chuanpu Hu; Yan Xu; Yanli Zhuang; Benjamin Hsu; Amarnath Sharma; Zhenhua Xu; Liping Zhang; Honghui Zhou (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

A CRISPR/Cas9 toolkit for efficient targeted base editing to induce genetic variations in rice - Bin Ren; Fang Yan; Yongjie Kuang; Na Li; Dawei Zhang; Honghui Lin; Huanbin Zhou (Science China Life Sciences, 2017)

Expression patterns of an isoflavone reductase-like gene and its possible roles in secondary metabolism in Ginkgo biloba - Cheng Hua; Li Linling; Xu Feng; Wang Yan; Yuan Honghui; Wu Conghua; Wang Shaobing; Liao Zhiqin; Hua Juan; Wang Yuping; Cheng Shuiyuan; Cao Fuliang (Plant Cell Reports, 2013)

Expression patterns of a cinnamyl alcohol dehydrogenase gene involved in lignin biosynthesis and environmental stress in Ginkgo biloba - Hua Cheng; Linling Li; Feng Xu; Shuiyuan Cheng; Fuliang Cao; Yan Wang; Honghui Yuan; Dezhi Jiang; Conghua Wu (Molecular Biology Reports, 2013)

Molecular cloning and function assay of a chalcone isomerase gene (GbCHI) from Ginkgo biloba - Hua Cheng; Linling Li; Shuiyuan Cheng; Fuliang Cao; Yan Wang; Honghui Yuan (Plant Cell Reports, 2011)